INDIVIDUAL ETHICS IN THE CONTEXT OF MODERN ORGANIZATIONS - Suprapti Widiasih (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
Individual ethics in modern organizations are a fundamental aspect that affects work culture, team effectiveness, and organizational reputation. This research aims to analyze the role of individual ethics in shaping a productive and sustainable work environment. Using a qualitative approach with a literature study method, this study examines the factors that affect individual ethics, ethical models in organizations, and ethical principles that need to be applied. The results of the study show that individual ethics are closely related to motivation, ability, role perception, and situational factors in the organization. The MARS (Motivation, Ability, Role Perception, Situational Factors) model is used to understand the interconnectedness between these factors in shaping an individual's ethical behavior in the workplace. In conclusion, the application of strong individual ethics contributes to the success of an organization and increases its competitiveness. Therefore, organizations need to create systems that support the development of individual ethics through policies, training, and organizational culture that are based on ethical values.